(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Internet Banking, also known as net-banking or online banking is an electronic payment system that enables the customer of a bank or a financial institution to make financial or non-financial transactions online via the internet. This service gives online access to almost every banking service, traditionally available through a local branch to the customers. Internet banking can be accessed by any individual who has registered for online banking at the bank, having an active bank account or any financial institution.